PENGELOMPOKAN PENYAKIT HIPERTENSI DI KOTA KUPANG MENGGUNAKAN METODE K-MEANS - Tedju, Yunior (STIKOM Uyelindo Kupang, 2022)
Hypertension is an event that causes a lot of data that has not been processed properly. According to the Central Bureau of Statistics of Kupang City, hypertension is in the top 10 with the highest number of sufferers in Kupang City. Through the official website, namely kupangkota.bps.go.id hypertension is in third place the number of diseases suffered by the community in 2018 with 28,701 cases and an increase of 6,935 in 2019 and of course it will increase in the following year. In this study clustering hypertension using the Data Mining method, namely k-Means clustering, the k-Means method can produce more accurate data in data grouping. The purpose of this study is to process and classify hypertension data so that it can help the government, especially the local Health Office, in classifying which areas have a large impact as swearing hypertension.